Posterior Reversible Encephalopathy Syndrome in a 20-Year-Old Female Admitted into the Intensive Care Unit (Journal of Enam Medical College, 2024)
Posterior Reversible Encephalopathy Syndrome (PRES) is a rare clinico-neuroradiological syndrome. Here we present a case of a 20-year-old lady who was admitted into our Intensive Care Unit (ICU) with respiratory distress, limb weakness, blurring of vision, four episodes of generalized tonic-clonic seizures, altered sensorium and headache on the14th day following Lower Segment Caesarian Section (LSCS) due to 38 weeks of pregnancy with severe pre-eclamptic toxaemia (PET). She was diagnosed as a case of PRES based on the clinical features along with findings on Magnetic Resonance Imaging (MRI). She was treated conservatively. Clinical condition of the patient was improved within 3 days. So, we conclude early recognition and proper management helps to reduce permanent neurological damage and thereby reduce morbidity and mortality.J Enam Med Col 2021; 11(2): 190−194